(untitled) (South East Asia Journal of Public Health, 2016)
Breast feeding and complementary feeding practices ultimately determine the nutritional status of newborn at the end of infancy. The objective of the present study was to find the possible causes of malnutrition in context of breastfeeding and complementary feeding practices adopted by families of infants aged 6-12 month old. A community-based, unmatched, case-controlled study was conducted involving 78 cases and 156 controls in the Raisen district of Madhya Pradesh, India. The study included infants aged 6- 12 months who were enrolled in the Integrated Child Development Scheme. Cases and controls were selected through a multi-staged sampling strategy. Cases were those with severe acute malnutrition and controls were those with no malnutrition as per the World Health Organization criteria. Data related to the breastfeeding, pre-lacteal feeding and complementary feeding practices were collected using a pre-tested questionnaire. Descriptive and bivariate analyses were carried out. P-value and Odds ratios were calculated. The proportion of exclusive breastfeeding among cases and control was 10.3% and 24.4% respectively. The high odds of malnutrition were related to lack of exclusively breastfeeding [COR(95% CI) = 4.69(2.50- 6.53)], lack of feeding semisolid food, less frequent complementary feedings [COR(95% CI) = 5.69(3.01- 8.93)], lack of hand washing by caregivers [COR(95% CI) =2.44 (1.10-3.19)], and lack of use of disinfected drinking water for infants. Proper health education should be imparted not only to mothers but also other family members involved in the childs care. South East Asia Journal of Public Health Vol.6(1) 2016: 32-39